Enzyme therapy and immune response in relation to CRIM status: the Dutch experience in classic infantile Pompe disease. Issue 2 (9th April 2014) - van Gelder, Carin M.; Hoogeveen‐Westerveld, Marianne; Kroos, Marian A.; Plug, Iris; van der Ploeg, Ans T.; Reuser, Arnold J. J.
Abstract: Background: Enzyme‐replacement therapy (ERT) in Pompe disease—an inherited metabolic disorder caused by acid α‐glucosidase deficiency and characterized in infants by generalized muscle weakness and cardiomyopathy—can be complicated by immune responses. Infants that do not produce any endogenous acid α‐glucosidase, so‐called CRIM‐negative patients, reportedly develop a strong response. We report the clinical outcome of our Dutch infants in relation to their CRIM status and immune response. Methods: Eleven patients were genotyped and their CRIM status was determined. Antibody formation and clinical outcome were assessed for a minimum of 4 years. Results: ERT was commenced between 0.1 and 8.3 months of age, and patients were treated from 0.3 to 13.7 years. All patients developed antibodies. Those with a high antibody titer (above 1:31, 250) had a poor response. The antibody titers varied substantially between patients and did not strictly correlate with the patients' CRIM status. Patients who started ERT beyond 2 months of age tended to develop higher titers than those who started earlier. All three CRIM‐negative patients in our study succumbed by the age of 4 years seemingly unrelated to the height of their antibody titer. Conclusion: Antibody formation is a common response to ERT in classic infantile Pompe disease and counteracts the effect of treatment. The counteracting effect seems determined by the antibody:enzyme molecular stoichiometry. The immune response may be minimized by early start of ERT and by immune modulation, as proposed by colleagues. The CRIM‐negative status itself seems associated with poor outcome.